Pexy of intraperitoneal LVAD driveline to relieve small bowel obstruction. Issue 2 (3rd December 2019) - Cresse, Stephen M.; Urrechaga, Eva M.; Cioci, Alessia C.; Banerjee, Monisha N.; Cahill, Anthony; Lieberman, Howard M.
Abstract: Background: Left ventricular assist device (LVAD) implantation is a lifesaving intervention in advanced heart failure. However, LVAD is not without complication. In this case, an inadvertent intraperitoneal driveline caused small bowel obstruction, subsequently requiring pexy of the driveline to the abdominal wall to avoid future complications. Case presentation: A 37‐year‐old male with worsening, nonischemic, dilated cardiomyopathy underwent LVAD implantation. Postoperative day (POD) 15 he developed small bowel obstruction, and abdominal exploration showed transition point at an inadvertently placed intraperitoneal LVAD driveline. The patient was LVAD‐dependent precluding removal, so the driveline was secured to the anterior abdominal wall. He subsequently improved and was discharged. Conclusions: While LVAD is increasingly common for heart failure patients, the tunneled driveline may inadvertently enter the peritoneal cavity where it can cause significant morbidity. In this case, we propose securing the driveline to the abdominal wall to prevent complications when LVAD removal is not an option.